Keabsahan Yuridis Perjanjian Pinjaman Online yang Tidak Terdaftar di Otoritas Jasa Keuangan - Triastarina Pratama Putri; Dewi Astutty M; Sunarjo Sunarjo; Fadilla Dwi Lailawati (University of Merdeka Malang, 2020)
The presence of lending and borrowing services based on information technology or peer to peer lending. The mushrooming of loans, especially illegal or unlicensed online loan applications, makes the risk of conflict even greater. The study, entitled “Juridical Legality of Online Loan Agreements that Are Not Registered at the Financial Services Authority”, has a problem formulation of how the form and validity of the agreement through online loans that are not registered with the OJK and how legal remedies can be taken when the debtor does not fulfill the agreement (default). The purpose of this study is to determine the form and validity of the agreement through online oans that are not registered with the OJK and to determine the legal remedies that can be done when the debtor does not fulfill the agreement (default).This approach uses the statute approachBased on the analysis conducted, it was concluded that the form and validity of the agreement through online loans that are not registered in the OJK is a written agreement, the agreement includes an underhand agreement. The validity of the agreement is valid as long as the parties do not renege on the agreement. Legal remedies that can be done if there is a default is to bring a summons or give a warning letter, if not carried out what was ordered in the summons, the parties who feel aggrieved can file a lawsuit against breach of contract to the court.